A inserção do componente currículo nos cursos de pedagogia do estado de São Paulo - Assunção, Alda Ribeiro Martins (2012)
The research aims to identify and analyze how the curriculum, as a curriculum component, is considered in the courses of Pedagogy in the State of São Paulo, based on their respective curriculum content and course descriptions. The analysis considers the institutions with a grade 3 in the National Survey of Student Performance (Enade) 2008, representing 41% of the total of 267 courses. Of the 110 courses surveyed, 65 indicate the presence of the Curriculum component, under a variety of names. To understand the processes that involved this context, the research started with a documental and bibliographic analysis on the subject, adopting the qualitative and quantitative approach. The work is supported by: Apple (2006), Chizzotti (2008), Chizzotti e Ponce (2011), Gatti (2009), Gimeno Sacristán (1999, 2000, 2007), Moreira (1990), Moreira and Silva (2009), Ponce (2006) and Silva (2003). Data collection was also made by means of semi-structured interviews with teachers of the components involving curriculum , which allowed the study to broaden the understanding of the political, pedagogical and technical interfaces of the component. The results, supported by content analysis, showed polysemy in the statements, which often differ on the emphasis on interfaces, pointing to multiple dimensions. It was also concluded, from the statements, that it is necessary to make adjustments in the course descriptions in order to broaden the number of hours allocated to curriculum components, considering the importance of this theme for the training of future educators